Penerapan Good Corporate Governance Pada Nazhir Tunai Yang Terdaftar Di Badan Wakaf Indonesia Studi Kasus Di Tabung Wakaf Indonesia Dan YPI Wakaf AL Azhar - Dede Dahlan (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2016)
There are many understanding of society, that cash waqf it should not be legal. So is the trust factor of people's money management institutions waqf (Nazhir) is still a constraint. Research conducted in Tabung Wakaf Indonesia (TWI) and Wakaf Al Azhar this analysis method, namely the principles of Good Corporate Governance (GCG). Here researchers using purposive sampling, followed by giving a score using the Likert Scale. To determine whether the data obtained in the field is valid or not, the researchers used a method tri angular source. The results of the assessment of GCG in TWI and Wakaf Al-Azhar obtain a total score of at Tabung Wakaf Indonesia amounting to 3.15. Then the bias is said that the implementation of GCG at TWI and Wakaf Al-Azhar declared "GOOD ENOUGH". While the results of the evaluation tri angular mention, that the data obtained from the results of research in the field both TWI and in Wakaf Al-Azhar, when compared with the corporate governance principles can be declared invalid according to the KNKG.